Real-World Evaluation of Demographics, Treatment Pattern, and Economic Burden of Heart Failure and Kidney Disease in Type 2 Diabetes Mellitus Patient Population in Dubai, United Arab Emirates - Alaaeldin Bashier; Mohamed Farghaly; Juwairia Yousif Alali; Amna Khalifa AlHadari; Yasmin Ajaz; Vani Krishna Warrier; Elamin Abdelgadir; Muhammad Hamed Farooqi; Sana Qamar; Mohamed Alsayed; Mohamed Samir Fahmy; Dali Tannouri; et al. (Dubai Diabetes and Endocrinology Journal)
Aims: The current study evaluated the demographics, clinical characteristics, treatment patterns, and economic burden of patients with type 2 diabetes mellitus (T2DM) with comorbidities (heart failure [HF], chronic kidney disease [CKD], and cardiovascular disease [CVD] without HF) in Dubai, United Arab Emirates (UAE). Methods: This observational, retrospective study collected data from January 01, 2014, to December 31, 2019, from the Dubai Real-World Claims Database (adults ≥18 years; at least 1 T2DM diagnosis claim). Patients were stratified into 5 cohorts: T2DM alone (cohort 1), T2DM and CKD (cohort 2), T2DM and CVD without CKD and HF (cohort 3), T2DM and HF (cohort 4), and T2DM with HF and CKD (cohort 5). An evaluation of demographics and clinical characteristics during pre-index period, as well as treatment patterns, healthcare resource utilization, and costs during the post-index period was conducted. Results: The sample had 374,271 patients with T2DM (age 43–56 years; male [72–84%]). Patients in cohorts 4 and 5 had Deyo-Charlson Comorbidity Index scores of 4.4 and 5.8, respectively. General practitioners (GPs) routinely prescribed biguanides for patients in cohorts 1–4 (24–38%), and insulin to patients in cohort 5 (27.7%). Prescription rates of novel antihyperglycemic drugs, such as glucagon-like peptide-1 (GLP-1 RA), were very low (∼2–8%) even in cohorts with cardiovascular and renal comorbidities (cohorts 2–5). A similar observation was noted with prescribing rates (0.6–4.4%) of sodium-glucose cotransporter-2 inhibitors (SGLT-2i) in cohorts 2–5. Endocrinologists preferred to prescribe GLP-1 RA and SGLT2i to T2DM patients with comorbidities. During the 5-year study period, median outpatient claims were the highest in cohort 5 (8.0 [range, 1.0–168.0]), followed by cohort 2 (5.5 [range, 1.0–52.0]). The median cost for inpatient claims was higher in cohort 5 (16,429 [range, 3,732–29,126] AED) compared to other cohorts. The median cost for drugs and procedures was highest in cohort 5 (4,525 [range, 38–31,546] AED and 2,297 [range, 56–105,074] AED, respectively). Conclusion: Continued and increased usage of drugs such as SGLT2i and GLP-1 RA with proven cardiorenal benefits could improve long-term outcomes and reduce associated healthcare costs in patients with T2DM and comorbidities in Dubai, UAE.